Study on groundwater quality at Kampung Jaya Gading, Kuantan, Pahang - Siti Noor Ain, Muhamad Husain (2012)
In Malaysia, groundwater is one of the sources of clean water, other than fresh river water and rain. Thus, this research had been done to determine the groundwater quality and also the effective type of well that can contribute to the good quality of groundwater. The parameters were considered such as manganese, iron, copper, zinc, chromium, lead, hardness, nitrate, total coliform and E.Coli in this study. The water samples were collected three times and from three different type of well such as open well, closed well, and bored well. The results were compared to the Interim National Drinking Water Quality Standard (INDWQS) to know the class of the groundwater for each well. The result showed that the groundwater had been contaminated by the chromium with concentration of 0.149 mg/L which found in open well. This result considered as relativelv not in verv hiizh concentration even the concentration of element is higher than the standard stated by lnterim National Drinking Water Quality Standard <lNDWOS). Meanwhile. For biolo1rical analvsis. Result showed that total coliform and E.coli have highest contamination which was found in open well with total coliform concentration 247.95 MPN/100 mL and E.coli concentration is 167.17 MPN/100 mL. As the conclusion, the groundwater quality was harmless from heavy metal concentration but highly contaminated with total coliform and E.coli.